Study of dosimetry in CT using head phantom - Mauricio Gomez; Priscila do Carmo Santana; Arnaldo Prata Mourão (Brazilian Journal of Radiation Sciences)
Non-invasive diagnosis methods based on x-ray attenuation, such as Computed Tomography (CT) has had since its discovery and the development of this technology, a rapid growth in radiology services. The quantity of dose deposited in patients, is still large, this type of examination is that reaches the highest levels of absorbed dose in the population. Legislation that regulates the levels of patient’s dose is only limited to a maximum amount deposited, depending the body region to be irradiated.  Therefore, it is necessary to determine the amount of absorbed dose on patients depending on the protocols of routine used in radiology services for propose an optimization of these based on the principles of radiation protection. Experiments were conducted to determine the profile of dose deposited in head routine exams for adult, using a cylindrical head phantom made of polymethylmethacrylate (PMMA). This standard phantom has four openings in peripheral and one central. Radiochromic film strips were introduced into each one of these openings to register the longitudinal dose profile in each region to determine the amount of deposited dose in the volume of the head phantom. A CT scanner with 64 channels of GE from the radiology department was used for scanning the head phantom. The scanning were done with voltages of 80, 100 and 120 kV, and dose index found were between 6.24 and 23.73 mGy. Analysis of image quality was performed, finding that all scan comply with the parameters acceptable in diagnosis for Brazilian legislation. It is propose an optimized protocol for exams by CT head for the voltage of 80 kV and images with 0.5% of noise index.